High fat, high sucrose diet causes cardiac mitochondrial dysfunction due in part to oxidative post-translational modification of mitochondrial complex II. (January 2015) - Sverdlov, Aaron L.; Elezaby, Aly; Behring, Jessica B.; Bachschmid, Markus M.; Luptak, Ivan; Tu, Vivian H.; Siwik, Deborah A.; Miller, Edward J.; Liesa, Marc; Shirihai, Orian S.; Pimentel, David R.; Cohen, Richard A.; et al.
Abstract: Background : Diet-induced obesity leads to metabolic heart disease (MHD) characterized by increased oxidative stress that may cause oxidative post-translational modifications (OPTM) of cardiac mitochondrial proteins. The functional consequences of OPTM of cardiac mitochondrial proteins in MHD are unknown. Our objective was to determine whether cardiac mitochondrial dysfunction in MHD due to diet-induced obesity is associated with cysteine OPTM. Methods and results : Male C57BL/6J mice were fed either a high-fat, high-sucrose (HFHS) or control diet for 8 months. Cardiac mitochondria from HFHS-fed mice ( vs. control diet) had an increased rate of H2 O2 production, a decreased GSH/GSSG ratio, a decreased rate of complex II substrate-driven ATP synthesis and decreased complex II activity. Complex II substrate-driven ATP synthesis and complex II activity were partially restored ex-vivo by reducing conditions. A biotin switch assay showed that HFHS feeding increased cysteine OPTM in complex II subunits A (SDHA) and B (SDHB). Using iodo-TMT multiplex tags we found that HFHS feeding is associated with reversible oxidation of cysteines 89 and 231 in SDHA, and 100, 103 and 115 in SDHB. Conclusions : MHD due to consumption of a HFHS "Western" diet causes increased H2 O2 production and oxidative stress in cardiac mitochondria associated with decreased ATP synthesis and decreased complex II activity. Impaired complex II activity and ATP production are associated with reversible cysteine OPTM of complex II. Possible sites of reversible cysteine OPTM in SDHA and SDHB were identified by iodo-TMT tag labeling. Mitochondrial ROS may contribute to the pathophysiology of MHD by impairing the function of complex II. This article is part of a Special Issue entitled "Mitochondria: From Basic Mitochondrial Biology to Cardiovascular Disease". Highlights: High fat, high sucrose (HFHS) diet increases cardiac mitochondrial H2 O2 production. HFHS diet decreases cardiac mitochondrial ATP synthesis and complex II activity. These HFHS diet-induced decreases are reversed by DTT ex vivo . HFHS diet leads to reversible oxidative modifications in 5 complex II cysteines.